Repeatability of regional pulmonary functional metrics of Hyperpolarized 129Xe dissolved‐phase MRI. Issue 4 (10th April 2019) - Hahn, Andrew D.; Kammerman, Jeff; Evans, Michael; Zha, Wei; Cadman, Robert V.; Meyer, Keith; Sandbo, Nathan; Fain, Sean B.
Abstract : Background: MRI of hyperpolarized 129 Xenon (HP 129 Xe) is increasingly utilized for investigating pulmonary function. The solubility of HP 129 Xe in lung tissue, blood plasma (Barrier), and red blood cells (RBC), with unique chemical shifts, enables spectroscopic imaging of potential imaging biomarkers of gas exchange and microstructural pulmonary physiology. Purpose: To quantify global average and regional repeatability of Barrier:gas, RBC:gas, and RBC:Barrier ratios derived from dissolved‐phase 129 Xe imaging and their dependence on intervisit changes in lung inflation volume. Study Type: Prospective. Population: Fourteen healthy volunteers. One subject was unable to complete the study resulting in 13 subjects for analysis (eight female, five male, ages 24–69, 53.8 ± 13.9). Field Strength: 1.5T. Assessment: Subjects were imaged using a 3D radial 1‐point Dixon method to separate Barrier and RBC component signals, at two different timepoints, with ~1 month between visits. RBC:Gas, Barrier:Gas, and RBC:Barrier measures were compared across time and with pulmonary function tests (PFTs). Statistical Tests: Repeatablilty was quantified using Bland–Altman plots, coefficient of repeatability, coefficient of variation (CV), and intraclass correlation coefficients (ICCs). Dependence of imaging measures on PFTs and lung volume was evaluated using Spearman and Pearson correlation coefficients, respectively. Statistical significance was determined by F‐test for intraclass correlations, and t ‐test for Spearman correlations and regression. Results: Mean RBC:Gas, Barrier:Gas, and RBC:Barrier had CVs of 19.2%, 20.0%, and 11.5%, respectively, and had significant ICCs, equal to 0.78, 0.79, and 0.92, respectively. Intervisit differences in RBC:Barrier were significantly correlated with intervisit differences in DLCO ( r = 0.93, P = 0.007). Significant correlations with intervisit lung volume differences and intervisit differences in mean RBC:Gas ( r = –0.73, P = 0.005) and Barrier:Gas ( r = –0.69, P = 0.009) were found. Data Conclusion: Three commonly used 129 Xe MRI‐based measures of gas‐exchange show good repeatability, particularly the Barrier:RBC ratio, which did not depend on lung inflation volume and was strongly associated with intervisit changes in DLCO . Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1182–1190.